Quantitative Data Processing in Scanning Probe Microscopy : SPM Applications for Nanometrology. - Klapetek, Petr.; ScienceDirect eBooks (Burlington : Elsevier Science, 2012)
Accurate measurement at the nano-scale - nanometrology - is a critical tool for advanced nanotechnology applications, where exact quantities and engineering precision are beyond the capabilities of traditional measuring techniques and instruments. Scanning Probe Microscopy (SPM) builds up a picture of a specimen by scanning with a physical probe; unrestrained by the wavelength of light or electrons, the resolution obtainable with this technique can resolve atoms. SPM instruments include the Atomic Force Microscope (AFM) and Scanning Tunneling Microscope (STM). Despite tremendous advances in Scanning Probe Microscopy (SPM) over the last twenty years, its potential as a quantitative measurement tool have not been fully realized, due to challenges such as the complexity of tip/sample interaction. In this book, Petr Klapetek uses the latest research to unlock SPM as a toolkit for nanometrology in fields as diverse as nanotechnology, surface physics, materials engineering, thin film optics, and life sciences. Klapetek's considerable experience of Quantitive Data Processing, using software tools, enables him to not only explain the microscopy techniques, but also to demystify the analysis and interpretation of the data collected. In addition to the essential principles and theory of SPM metrology, Klapetek provides readers with a number of worked examples to demonstrate typical ways of solving problems in SPM analysis. Source data for the examples as well as most of the described open source software tools are available on a companion website.
Motivation -- Instrumentation Principles -- Data Models -- Basic Data Processing* -- Dimensional Measurements* -- Force and Mechanical Properties -- Friction and Lateral Forces -- Electrostatic Fields* -- Magnetic Fields -- Local Current Measurements* -- Thermal Measurements -- Optical Measurements -- Sample Data Files -- Numerical Modeling Techniques.
Print version record.
Elsevier
Keywords: Scanning probe microscopy -- Data processing; Qualitative research -- Data processing; Scanning probe microscopy; SCIENCE -- Nanoscience; TECHNOLOGY & ENGINEERING -- Nanotechnology & MEMS; Scanning probe microscopy; Scanning probe microscopy -- Data processing; Electronic books